MENINJAU PERMASALAHAN RENDAHNYA KUALITAS PENDIDIKAN DI INDONESIA DAN SOLUSI - Fitria Nur Auliah Kurniawati (Fakultas Keguruan dan Ilmu Pendidikan, 2022)
This article is written to discuss the currently low quality of Indonesian education. In fact, education is something that is agreed upon to be the main thing in any nation. The quality of education in a nation is one of the determinants of the nation's progress. In other words, the progress of a nation or country can be seen from the quality of education in that nation and country. Therefore, this paper describes what problems Indonesia faces that can hinder the realization of a good quality education. Then it also describes how solutions can be made as an effort to overcome the problems of education in Indonesia. This study the authors used a qualitative method, namely by conducting a literature review. The author collects data and information from trusted journals and books and is in accordance with the discussion of this article. With this paper, it is hoped that it will raise awareness from each individual to build a better and more advanced Indonesia in order to prepare quality humans